ARCHIVES PUBLICATION AND EXHIBITION VIRTUALISATION BY ANRI - Noor, Muhammad Usman; Grataridarga, Niko (Record and Library Journal, 2019)
Background of the study: This study discusses the archival publication virtual services through exhibitions, published by ANRI (National Archives of the Republic of Indonesia). This study will analyze publication of content displayed through the virtual archival exhibition.Purpose: The aim is to look at aspects of the publication of archives, selecting and uploading information or document to the web or the site, repackaging information, and using technology. Archived publication is the dissemination of information about archives for the community, one kind of activities that are by holding a virtual exhibition. The virtual exhibition Allows visitors in the number of simultaneous accesses to one collection entity and Provides information quickly intervening and mainly via the web.Method: This study uses qualitative methods of content analysis. Methods of collecting the data through observation on ANRI Virtual Exhibition and literature studies.Findings: The discussion was further reviewed restaurants by using perspectives on aspects of archival publications, archival exhibitions, and archive exhibition virtualization. The results that can be obtained are ANRI roommates virtual conducts archival exhibitions through the JIKN at https://jikn.go.id. Displaying two themes, the history of the President of the Republic of Indonesia and the Treasury of the UNESCO Certificate of Archives. The virtual archival exhibition is an excellent publication from ANRI to present information from the archive so that it can be easily accessed by the public. But at this virtual archival exhibition, there are still several menus and features are still empty.Conclusion: The advice that can be given is to add back the content, features and media information offered to visitors through the virtual archival exhibition. The addition of content managers, is also competencies needed to the make virtual archival exhibitions more interactive